Segmental overgrowth and aneurysms due to mosaic PDGFRB p.(Tyr562Cys). Issue 5 (8th March 2021) - Chenbhanich, Jirat; Hu, Yan; Hetts, Steven; Cooke, Daniel; Dowd, Christopher; Devine, Patrick; ,; Russell, Bianca; Kang, Sung Hae L.; Chang, Vivian Y.; Abla, Adib A.; Cornett, Patricia; et al.
Abstract: Activating variants in the platelet‐derived growth factor receptor β gene ( PDGFRB ) have been associated with Kosaki overgrowth syndrome, infantile myofibromatosis, and Penttinen premature aging syndrome. A recently described phenotype with fusiform aneurysm has been associated with mosaic PDGFRB c.1685A > G p.(Tyr562Cys) variant. Few reports however have examined the vascular phenotypes and mosaic effects of PDGFRB variants. We describe clinical characteristics of two patients with a recurrent mosaic PDGFRB p.(Tyr562Cys) variant identified via next‐generation sequencing‐based genetic testing. We observed intracranial fusiform aneurysm in one patient and found an additional eight patients with aneurysms and phenotypes associated with PDGFRB‐ activating variants through literature search. The conditions caused by PDGFRB‐ activating variants share overlapping features including overgrowth, premature aged skin, and vascular malformations including aneurysms. Aneurysms are progressive and can result in morbidities and mortalities in the absence of successful intervention. Germline and/or somatic testing for PDGFRB gene should be obtained when PDGFRB activating variant‐related phenotypes are present. Whole‐body imaging of the arterial tree and echocardiography are recommended after diagnosis. Repeating the imaging study within a 6‐ to 12‐month period after detection is reasonable. Finally, further evaluation for the effectiveness and safety profile of kinase inhibitors in this patient population is warranted.